English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Remove the parenthesis in each of the following expressions amd simplify where possible. 8d-(-7c-2d)

2007-09-08 03:23:14 · 9 answers · asked by Anonymous in Science & Mathematics Mathematics

9 answers

multipling the negative through the parenthesis gives you

8d --7c--2d

double negative is a positive so you really have

8d + 7c + 2d

simplify (add the like expressions)

10d + 7c

2007-09-08 03:28:21 · answer #1 · answered by Andy 1 · 0 1

The answer is 6d+7c because the 2 negatives become a positve and then you subtract 2d from 8d and you get 6d + 7c

2007-09-08 03:38:10 · answer #2 · answered by nicoleem1992 1 · 0 0

8d + 7c + 2d
= 10 d + 7c

2007-09-08 03:30:20 · answer #3 · answered by CPUcate 6 · 0 0

8d + 7c + 2d = 10d + 7c

2007-09-11 19:27:38 · answer #4 · answered by Como 7 · 0 0

8d - (-7c - 2nd) = 8d + 7c + 2nd = 7c + 10d to learn, Subsitute d = 2, c = 3 into 8d - (-7c - 2nd) 8 x 2 - (-7 x 3 - 2 x 2) = sixteen - (-21 - 4) = sixteen - (-25) = sixteen + 25 = 40-one to learn, Subsitute d = 2, c = 3 into 7c + 10d 7 x 3 + 10 x 2 = 21 + 20 = 40-one hence the equation is right. desire this helps.

2016-10-10 04:48:39 · answer #5 · answered by cumberledge 3 · 0 0

8d-(-7c-2d)
=8d+7c+2d
=10d+7c. ANS.

2007-09-08 03:38:38 · answer #6 · answered by Anonymous · 0 0

8d+7c+2d
10d+7c

2007-09-08 03:28:40 · answer #7 · answered by xtianonil 2 · 0 1

You have to tell what the letters stand for but when to numbers or a number and a variable are together without an operation you multiply 8*s d -(7*sc-2*sd)

2007-09-08 03:33:26 · answer #8 · answered by Anonymous · 0 0

8d-(-7c-2d)
= 8d+7c+2d
=10d+7c

2007-09-08 03:29:22 · answer #9 · answered by Anonymous · 0 0

fedest.com, questions and answers